Followership : what it takes to lead - Schindler, James H. (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
Followers dominate all organizations, but a preoccupation with leaders hinders the consideration of the importance of followers and the relationship between followers and leaders. The topic of this book is how to become a better leader by becoming a better follower. The book includes chapters on the topics of: leadership theory, followership theory, preparation for the job, understanding what is required for the job, communication, initiative, positive attitude, responsibility, problem solving, and teamwork. This book provides suggestions for becoming an exemplary follower which will demonstrate and manifest the skills associated with leadership and bridge the gap between leadership training and followership.
1. Introduction to leadership theory -- 2. Followership theory -- 3. Preparation for the job -- 4. Understanding what is required -- 5. Communications -- 6. The three "I"s of initiative -- 7. Positive attitude -- 8. Responsibility -- 9. Problem solving -- 10. Teamwork -- About the author -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 93-96) and index.
Title from PDF title page (viewed on December 7, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Followership; followership; followership theory; leadership; leadership theory; mentoring; success; Electronic books